THE INFLUENCE OF INFORMATION TECHNOLOGY ON HIGHER EDUCATION IN PAKISTAN - Sain, Zohaib Hassan (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
This study aims to analyze the impact of information technology (IT) on higher education in Pakistan. IT has emerged as a valuable tool, improving access and providing opportunities for individuals to pursue education and careers. The specific objectives are to explore the role of IT in Pakistan's education sector, propose effective integration measures, examine how individuals utilize IT for educational enhancement, and investigate strategies for generating innovative research ideas. The discussion will focus on the structure, accessibility, quality, and future prospects of IT in Pakistan. Emphasizing the importance of quality education, the study highlights the need to produce knowledgeable, skilled, motivated, and ethically responsible individuals to achieve national development goals. The Higher Education Commission (HEC) has been instrumental in advancing the higher education system by transforming institutions into centers for advanced education, research, and development through IT integration. However, the study acknowledges challenges that need addressing, including infrastructure improvements, qualified teachers, and a stronger emphasis on quality. Overall, the findings suggest that IT has significant potential to enhance higher education in Pakistan, but concerted efforts are required to overcome existing challenges.